Functionalization of Cash Waqf for Solving Poverty Problems in Indonesia - Dodi Yarli; Lina Pusvivasari; Mohamad Anton Athoillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Increased economic power and growth in a country can be signaled from indicators of poverty levels and economic weakness. Poverty is the main reason for moral hazart and the unstable economy of a nation. Cash waqf exists to solve and overcome these socio-economic problems. Cash waqf has universal power and strength where every individual will be able to donate wealth without certain limits. Cash waqf is also very strategic in building and presenting employment areas and reducing unemployment in selective production activities according to Sharia rules and benefits. waqf has the potential to empower the real sector and strengthen economic fundamentals. Through the instrument of cash waqf, poverty alleviation can be overcome through the hands of the Government in the channel of community empowerment programs. The target of waqf in Indonesia is actually able to create social welfare for the community as the goal of economic justice, hence the need for effective waqf nadzir governance. Cash waqf has tremendous economic potential to take care of the mustadh'afiin group as well as to alleviate poverty, especially because the sociological conditions of the Indonesian people are Muslim so that waqf funds that can be collected from the community are very possible